Analisis Penerapan Activity Based Costing untuk Penentuan Harga Pokok Produk Pada Muthia Gebyok - anni safitri; Junirin, Junirin (Jurnal Akuntansi & Keuangan Unja, 2024)
The purpose of this study is to determine the cost of Muthia Gebyok products using traditional methods and also to calculate the cost of products using the Activity Based Costing method. This type of research is descriptive research with a case study approach. Data collection techniques use business operations reports and interviews. The results of this study state that using the Activity Based Costing method in calculating costs per unit provides more accurate information and can be used to set competitive selling prices, understand competition better, provide more precise profit information, and make the planning process more effective.